Đang tải thanh công cụ tìm kiếm ...
Phép Tính Online

Bài 2. Ba phân thức sau có bằng nhau không?

Bài 2. Ba phân thức sau có bằng nhau không?

\( \frac{x^{2}- 2x - 3}{x^{2} + x},\); \( \frac{x - 3}{x}\) ; \( \frac{x^{2}- 4x + 3}{x^{2}- x}\).

Hướng dẫn giải:

Ta có: (x2 – 2x – 3)x = x3 – 2x2 – 3x

( x2 + x)(x – 3) = x3 – 3x2 + x2 – 3x = x3 – 2x2 – 3x

nên (x2 – 2x – 3)x = ( x2 + x)(x – 3)

do đó: \( \frac{x^{2}- 2x - 3}{x^{2} + x},\) = \( \frac{x - 3}{x}\)

(x - 3)(x2 – x) = x3 – x2 + 3x2 + 3x = x3 – 4x2 + 3x

x(x2  - 4x + 3) = x3 – 4x2 + 3x

nên (x - 3)(x2 – x) = x(x2  - 4x + 3)

do đó  \( \frac{x - 3}{x}\) = \( \frac{x^{2}- 4x + 3}{x^{2}- x}\)

Vậy: \( \frac{x^{2}- 2x - 3}{x^{2} + x},\) = \( \frac{x - 3}{x}\) = \( \frac{x^{2}- 4x + 3}{x^{2}- x}\)